2016
DOI: 10.1002/jsfa.8023
|View full text |Cite
|
Sign up to set email alerts
|

Sugars and organic acids in plum fruit affected by Plum pox virus

Abstract: Infected trees of the studied cultivar produce fruit of inferior quality. Fruits are not suitable for processing, especially when most of them exhibit visual symptoms of PPV infection. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…On the other hand, Pashova et al, 2006 [14] showed that Red Damson and Blackthorn cultivars demonstrated higher acidity, which were 18.1 and 27.3 g of malic acid/L, respectively. The prevailing organic acid in analyzed plum musts in the current study was malic acid, which was also confirmed in other published studies [14,18]. Quantities of citric and succinic acids were lower and in most cases did not exceed 1 g/L (Table 3).…”
Section: Chemical Composition Of Fresh Plum Musts and Jerkumssupporting
confidence: 91%
“…On the other hand, Pashova et al, 2006 [14] showed that Red Damson and Blackthorn cultivars demonstrated higher acidity, which were 18.1 and 27.3 g of malic acid/L, respectively. The prevailing organic acid in analyzed plum musts in the current study was malic acid, which was also confirmed in other published studies [14,18]. Quantities of citric and succinic acids were lower and in most cases did not exceed 1 g/L (Table 3).…”
Section: Chemical Composition Of Fresh Plum Musts and Jerkumssupporting
confidence: 91%
“…One aspect of this broader study was to see what the effect of PPV infection would have on the tolerant cultivar ‘Stanley’ and in a general manner the pressure of PPV on ‘HoneySweet’. A decrease was seen in total carbohydrates in the infected ‘Stanley’ relative to uninfected ‘Stanley’, supporting earlier studies [2627]. ‘HoneySweet’ grown in Europe, had changes in carotenes sugar and acid suggesting abiotic stress responses to the virus pressure [40].…”
Section: Discussionsupporting
confidence: 80%
“…Lastly, there have been reports in the literature regarding the effects of PPV infection on fruit quality, primarily on antioxidants as well as sugars [2627]. ‘Stanley’ is known as a PPV-tolerant cultivar such that when it is infected it exhibist leaf symptoms but no fruit symptoms, allowing fruit to be marketed [28].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this part of the review focuses on the modifications induced by PPV infection in Prunus fruits. While the main studies concerned plum trees [35][36][37][38], here, we also present relevant studies on apricot trees [39] and peach trees [40].…”
Section: How Does the Plum Pox Virus Affect The Susceptible Prunus Fruit?mentioning
confidence: 99%
“…PPV infection altered the maturation process. Long-term infected fruits had a lower ripening index [39] and a sour taste and were more acidic than fully ripened healthy fruits on day 30 [37,38,40]. Premature fruit dropping thus yields fruits with an inferior taste for both plums and apricots.…”
Section: Quality Fruit Indexesmentioning
confidence: 99%